Analisis Pengaruh Website Quality terhadap Kepuasan Pengguna dengan Menggunakan Metode WebQual 4.0 - Kenny Roz (Jurnal Manajemen dan Kewirausahaan, 2020)
Online business competition requires business people who are able to improve the quality of the website to win market share. WebQual is a method developed by Barnes and Vidgen that measures website quality based on usability, information quality, and service interaction. This study aims to examine and analyze the effect of website quality on Traveloka's online booking site on user satisfaction. This research uses a quantitative approach with multiple regression analysis. Sampling uses a purposive sampling that is students in the city of Malang who have made online reservations on the Traveloka site with a sample of 186 respondents. Based on the results of data analysis found that: 1) usability has a positive and significant effect on user satisfaction, 2) information quality has a positive and significant effect on user satisfaction, and 3) the quality of service interactions has a positive and significant effect on user satisfactionhttps://doi.org/10.26905/jmdk.v8i1.3782